Banned drugs in sport: does the International Olympic Committee (IOC) list need updating? - Mottram, D. R. (Sports Medicine, 1999)
The International Olympic Committee (IOC) published the first list of doping classes in 1967. Since that time, there have been significant problems associated with doping control in sport. Sport is a high profile, internationally recognised activity. However operational inconsistencies exist between countries and between sports federations. Endogenous substances, such as testosterone, human growth hormone (hGH) and erythropoietin (Epo) present particular problems in determining what constitutes 'normal' levels in athletes. In addition, there is no reliable method available for the detection of hGH and Epo through urine testing. Athletes continue to test positive for banned drugs that are available over-the-counter despite their having been taken inadvertently, without intent to enhance performance. Marijuana use is becoming widespread in society and the impact of this in sport is becoming evident.